4/15 = 0.267
8/25 = 0.32
0.267/0.32 = 0.834375
Answer:
!["i"](https://tex.z-dn.net/?f=%22i%22)
Step-by-step explanation:
![i =\sqrt{-1} \\i^{2}= -1\\\\i^{3}= -i\\\\i^{4}= 1\\\\i^{5}= i\\](https://tex.z-dn.net/?f=i%20%3D%5Csqrt%7B-1%7D%20%5C%5Ci%5E%7B2%7D%3D%20-1%5C%5C%5C%5Ci%5E%7B3%7D%3D%20-i%5C%5C%5C%5Ci%5E%7B4%7D%3D%201%5C%5C%5C%5Ci%5E%7B5%7D%3D%20i%5C%5C)
the cycle repeats every 4
19/4 = 4.75
16 is divisible by 4 plus three more
thus
but you problem has a minus in front so "i"
Answer:
A function is a rule that assigns each value of the independent variable to exactly one value of the dependent variable.
Step-by-step explanation:
hope that it helped you
<span>19+52−0−(1)(5)</span>
<span><span><span>71−0</span>−<span><span>(1)</span><span>(5)
</span></span></span></span><span><span>71−<span><span>(1)</span><span>(5)
</span></span></span></span><span><span>71−5
</span></span><span><span>Answer:
66</span></span>
Answer:
a = 1 b = -1.
Step-by-step explanation:
Suppose the quotient when you divide x^4+x^3+ax+b by x^2 + 1 is
x^2 + ax + b then expanding we have:
(x^2 + 1)(x^2 + ax + b)
= x^4 + ax^3 + bx^2 + x^2 + ax + b
= x^4 + ax^3 + (b + 1)x^2 + ax + b Comparing this with the original expression:
x^4 + x^3 + 0 x^2 + ax + b Comparing coefficients:
a = 1 and b+ 1 = 0 so b = -1.